2021
DOI: 10.1080/21655979.2021.1931643
|View full text |Cite
|
Sign up to set email alerts
|

Insulin reverses choriocarcinoma 5- fluorouracil resistance

Abstract: Choriocarcinoma (CC) is a gestational trophoblastic tumor secondary to a gravid or non-gravid pregnancy. It is characterized by rapid growth, high invasion, and high metastatic potential and chemotherapy resistance that significantly affect survival rate of CC patients. Insulin is implicated in alleviation of chemotherapy resistance in CC. However, the mechanism of reversing resistance in CC has not been explored. Our purpose was to explore insulin effect on 5-fluorouracil (5-FU) resistance in CC and elucidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…High intracellular cytotoxic drug concentration in tumor cells allows killing of tumor cells but a growing number of evidence show an increase in chemotherapy resistance on account of P-gp upregulation. For this reason, P-gp expression in tumor cells may influence the clinical response to chemotherapy [26]. In our model, we showed that hinokitiol treatment at specified concentration suppresses expression of P-gp that corresponded to a substantial decrease of drug efflux activity.…”
Section: Discussionmentioning
confidence: 73%
“…High intracellular cytotoxic drug concentration in tumor cells allows killing of tumor cells but a growing number of evidence show an increase in chemotherapy resistance on account of P-gp upregulation. For this reason, P-gp expression in tumor cells may influence the clinical response to chemotherapy [26]. In our model, we showed that hinokitiol treatment at specified concentration suppresses expression of P-gp that corresponded to a substantial decrease of drug efflux activity.…”
Section: Discussionmentioning
confidence: 73%
“…According to a previous study [ 25 ], 1 × 10 6 of HCT 8 as well as SW620 cells were seeded into a 24-well upper chamber precoated with Matrigel (Corning Inc., USA). After 48 h, the upper chamber cells were removed, and the invading cells were fixed with methanol and stained with crystal violet.…”
Section: Methodsmentioning
confidence: 99%
“…Cell migration and invasion were measured using transwell assays [ 17 ]. The lower chamber contained 400 μL medium containing 10% fetal calf serum, and 200 μL cell suspension was added to the upper chamber (Matrigel was used for invasion determination and migration determination without Matrigel).…”
Section: Methodsmentioning
confidence: 99%